UNDERSTANDING APPLIED LINGUISTICS - Nguyễn Tất Thắng (Tạp chí Khoa học Đại học Đà Lạt)
Applied linguistics has played a significant role in different fields in language studies, such as researching and teaching languages, assessing languages, language policy planning, etc. Therefore, it is essential to understand applied linguistics and its research outcomes relating to language studies. This paper primarily tackles fundamental issues relating to applied linguistics in order to provide readers with basic knowledge of this branch of linguistics.